PENGARUH COMPUTER ATTITUDE DAN COMPUTER ANXIETY TERHADAP MINAT MAHASISWA AKUNTANSI UPN "VETERAN" JAKARTA MENGGUNAKAN APLIKASI AKUNTANSI - Sorta Nadya, (2024)
This research was conducted with the aim of finding out how computer attitude and computer anxiety influence students' intention to use accounting applications. This research was conducted using a quantitative approach. Data collection was carried out by distributing questionnaires to accounting students at the Universitas Pembangunan Nasional "Veteran" Jakarta with a sample size of 69 students. Data processing uses Microsoft Excel and the SmartPLS 4 application. The results of this research prove that (1) Computer Attitude has a positive and significant effect on students' interest in using accounting applications (2) Computer anxiety has a positive and significant effect on students' interest in using accounting applications.